Identity and the state in Malaysia - Barlocco, Fausto (New York : Routledge, 2014)
'Using the case study of the Kadazan of Sabah, a region in the Malaysian section of Borneo, this book examines national, ethnic and local identities in post-colonial states. It shows the importance of the connection between lived experience and identity and belonging, and by doing so, provides a deeper and fuller explanation of the apparently contradictory conflict between different collective forms of identification and the way in which they are employed in reference to everyday situations. Based on ethnographic fieldwork and historical analysis, the book reconstructs the development of the cultural forms and labels associated with the collective identities studies. The author employs an approach that sees collective identification as an expression of everyday practices and that stresses the importance of participation and familiarity between forms of identification and lived experience. In this context, he considers anthropological debates about state-minorities relations and issues of'dignity' and'respect'. Explaining state-minority relations in Malaysia and more generally in other post-colonial realities, the insights presented are highly relevant to other cases of conflicting allegiances and identity politics in settings of post-colonial nation-building'--
Introducing the'field' : the ethnographic setting of the research -- The formation of the Kadazan : ethnic identities in pre-colonial, colonial and early post-colonial Sabah -- The Dusunic peoples and Malaysian nation-building (1967-present) -- Self and other : collective identities between citizenship rights and illegal immigration -- Media and belonging to the nation -- The constitution of village belonging through leisure sociality -- A tale of two celebrations : the Pesta Kaamatan as a site of struggle between the Dusunic peoples and the state.
Includes bibliographical references and index.
Keywords: Dusun (Bornean people) -- Ethnic identity; Identity politics -- Malaysia -- Sabah; Ethnology -- Malaysia -- Sabah; National characteristics, Malaysian; Sabah -- Ethnic relations; Malaysia -- Ethnic relations; Malaysia -- Cultural policy